THE EFFECT OF AUDIT QUALITY AND GOOD CORPORATE GOVERNANCE TOWARDS DIVIDEND POLICY IN PUBLIC COMPANIES IN INDONESIA - Sihombing, Tanggor; Widono, Ronald (Universitas Multimedia Nusantara, 2023)
Abstract - The purpose of this study is to find the relationship between audit quality and good corporate governance (GCG) on dividend policy. Where the supervision provided by the company's independent auditors and independent board of commissioners has an impact on the returns received by investors in the form of dividends. The study was conducted using purposive sampling technique, taking 141 samples of non-financial public companies in Indonesia from the period of 2017-2019. The data were processed using the STATA program. The results of this study show evidence that the audit quality variable with the proxy of the Big 4 public accounting firm has a positive and significant effect on dividend policy. Which may be resulted from a better quality of supervision thus reducing agency conflicts. However, for the GCG variable, there is no evidence of an influence on dividend policy which may be resulted from different proxy variables. Keywords: Audit Quality; Good Corporate Governance; Dividend Policy; Independent Commissioner